The physics of deformation and fracture of polymers - Argon, Ali S. (Cambridge : Cambridge University Press, 2013)
A physical, mechanism-based presentation of the plasticity and fracture of polymers, covering industrial scale applications through to nanoscale biofluidic devices.
4.2.1 The generalized Hookes law4.2.2 Orthorhombic crystals or orthotropic solids; 4.2.3 Hexagonal crystals; 4.2.4 Cubic crystals; 4.2.5 Isotropic materials; 4.2.6 Temperature and strain dependence of elastic response; 4.3 Theoretical determination of elastic constants of polymers; 4.3.1 Glassy polymers; 4.3.2 Crystalline polymers; 4.4 Elastic response of textured anisotropic polymers; 4.5 Elastic properties of heterogeneous polymers; 4.5.1 Methods of estimating the elastic properties of heterogeneous polymers; 4.5.2 The self-consistent method; 4.5.3 The Eshelby inclusion method; References.
5 Linear viscoelasticity of polymers.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Polymers -- Fracture; Polymers -- Plastic properties; Plastics